X-ray diagnosis of juvenile chronic oligoarthritis - Aleksei N. Kozhevnikov; Nina A. Pozdeeva; Mikhail A. Konev; Olga N. Maricheva; Konstantin A. Afonichev; Gennadiy A. Novik (Бюллетень сибирской медицины, 2017)
Juvenile arthritis continues to be a serious diagnostic problem of pediatric rheumatology despite the improvement of clinical, immunological and instrumental methods of examination. Clinical heterogeneity, nonspecificity of instrumental picture and limited application of some examination methods account for the diagnostic difficulties of articular pathology in young children. Chronic oligoarthritis in young children presents a particular challenge due to a frequent vague onset and minimally symptomatic course which can result in a late diagnosis and a high risk of early disability. This paper identifies the problem of diagnosis of childhood arthropathy in relation to its informative value and the practical and clinical significance of basic instrumental methods of chronic arthritis visualization. Special attention is paid to particular roentgenologic features and interpretation of MR images in diagnosis of juvenile olighoarthritis. This article aims at systematizing and expanding the views of pediatricians and rheumatologists on the importance of radiography methods in the diagnosis of joint pathology in children.